2016
DOI: 10.1017/s147355041600015x
|View full text |Cite
|
Sign up to set email alerts
|

SEM morphological studies of carbonates and the search for ancient life on Mars

Abstract: Next space missions will investigate the possibility of extinct or extant life on Mars. Studying the infrared spectral modifications, induced by thermal processing on different carbonate samples (recent shells and fossils of different ages), we developed a method able to discriminate biogenic carbonates from their abiogenic counterparts. The method has been successfully applied to microbialites, i.e. bio-induced carbonates deposits, and particularly to stromatolites, the laminated fabric of microbialites, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Finally, in the presence of all DNAs, the biomorphs synthesized at a high CO 2 concentrations presented the biotic-type calcite and vaterite polymorphs, whereas the biomorphs in RTP conditions only presented the calcite polymorph (Table ). Among minerals, CaCO 3 is of great interest because organisms from all kingdoms are able to biomineralize it, generally in the calcite and aragonite polymorphs, and this finding is considered the most ancient evidence of life, although they can be synthesized biotically and abiotically. ,, The polymorph calcite (microbially induced) is a biogenic mineral that has been conserved in organisms for at least 500 million years and is present in most organisms. Our results showed that the CaCO 3 biomorphs obtained in the presence of genomic DNA correspond precisely to the calcite polymorphism in all conditions (Table ). This is an important datum as it can explain the reason why this polymorphism in fossils is found in the five kingdoms in nature.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Finally, in the presence of all DNAs, the biomorphs synthesized at a high CO 2 concentrations presented the biotic-type calcite and vaterite polymorphs, whereas the biomorphs in RTP conditions only presented the calcite polymorph (Table ). Among minerals, CaCO 3 is of great interest because organisms from all kingdoms are able to biomineralize it, generally in the calcite and aragonite polymorphs, and this finding is considered the most ancient evidence of life, although they can be synthesized biotically and abiotically. ,, The polymorph calcite (microbially induced) is a biogenic mineral that has been conserved in organisms for at least 500 million years and is present in most organisms. Our results showed that the CaCO 3 biomorphs obtained in the presence of genomic DNA correspond precisely to the calcite polymorphism in all conditions (Table ). This is an important datum as it can explain the reason why this polymorphism in fossils is found in the five kingdoms in nature.…”
Section: Resultsmentioning
confidence: 53%
“…The process of crystalline mineral formation, like calcium minerals, has been considered to be a biomarker of the existence of life on Earth and other planets like Mars. The crystalline minerals of Ca 2+ could display a biotic (microbially induced) or an abiotic origin as shown for Mars research in space. Identifying the origin and polymorphs of calcium minerals is not a trivial effort because detection of biomolecular markers in crystalline minerals provides valuable information on the possible existence of life on Earth. In this sense, several authors have proposed that the minerals obtained from controlled mineralization processes can be used as biomarkers as they fulfill characteristics that are different from abiotic minerals with the same chemical composition .…”
Section: Resultsmentioning
confidence: 99%
“…The lack of detailed insight into the preservation processes of organic matter, or biosignatures in general, within dolomitized carbonate lithologies is further complicated when applied to astrobiology. Carbonate lithologies are a recognized astrobiology target for Mars exploration (Cady et al, 2003;Summons et al, 2011;D'Elia et al, 2017). The primary science goal of the Mars 2020 mission is to determine whether life existed on Mars by seeking signs of extinct life in the rock record (Mustard et al, 2013;Williford et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the analysis of a peculiar class of materials, that we may call ‘white soft minerals’ (WSM) including calcite, magnesite, gypsum, talc, might represent a key point in panspermia theory, as these materials are often associated with the presence of organic matter (Gooding et al 1988; Pizzarello et al 2006; Orofino et al 2009; Yabuta et al 2014; D'Elia et al 2017).…”
Section: Introductionmentioning
confidence: 99%